Spiro‐Linked Molecular Hole‐Transport Materials for Highly Efficient Inverted Perovskite Solar Cells. Issue 3 (14th November 2019) - Wang, Chuan; Hu, Jinlong; Li, Chaohui; Qiu, Shudi; Liu, Xianhu; Zeng, Linxiang; Liu, Chuntai; Mai, Yaohua; Guo, Fei
Abstract : Spiro‐linked compounds have been used as benchmark hole‐transport materials (HTMs) for the construction of efficient normal architecture (n‐i‐p) perovskite solar cells (PSCs). However, the heavy reliance on the use of dopants not only complicates the device fabrication but imposes long‐term stability concern of the devices. Herein, it is reported that solution‐processed dopant‐free spiro molecules can serve as superior HTMs to fabricate efficient inverted (p‐i‐n) PSCs. Rational choice of orthogonal solvent allows us to solution deposit uniform and pinhole‐free perovskite films without compromising the hole‐extraction capability of the spiro‐based interface layers. To illustrate the generality of the strategy, three spiro‐linked molecules are investigated side by side as HTMs in one‐step solution‐processed CH3 NH3 PbI3 PSCs. Due to the favored energy‐level alignment and high hole mobility, solar cells based on the HTM of spiro‐TTB yield a high efficiency of 18.38% with open‐circuit voltages ( V OC ) up to 1.09 V. These results suggest that small molecular HTMs commonly developed for normal structure devices can be of great potential to fabricate cost‐effective and highly efficient inverted PSCs. Abstract : Herein, it is demonstrated that solution‐processed dopant‐free spiro molecules can serve as superior hole‐transport materials (HTMs) to fabricate efficient inverted (p‐i‐n) perovskite solar cells. An entirely solution process is achieved by rational choice of orthogonal solvent, which allows to deposit uniform and pinhole‐free perovskite films without compromising the hole‐extraction capability of the spiro interlayers.